Diversité et évolution des capitalismes en Amérique latine. De la régulation économique au politique - Robert Boyer (Revue de la Régulation)
The introductory article of this thematic issue offers a brief history of regulationist research on Latin America from the early 80's to 2011. The related works have extended and enriched the concepts and methods initially elaborated for mature industrial countries. Rentier regimes are orthogonal to the Fordist regimes, the nature of international integration largely determines the dynamics of domestic institutional forms, the large size of informal work makes problematic the institutionalization of the wage labor nexus, the social insurance systems are idiosyncratic, finally weak States make difficult institutional change. Even though they share most of these features Argentina, Brazil, Chile and Mexico are exploring largely original trajectories, which result not only of differences in natural endowments, but also of specific political alliances and the related institutionalized compromises, implicit or explicit. The polity becomes dominant during structural crises, as evidenced by Argentina after 2001. This teaching goes beyond Latin America since it allows the explanation of some of the channels of political regulation. It is a call for a deeper study of the complex processes that shapes the way out of structural crises and this is a central issue of this decade.